2022
DOI: 10.1186/s43163-022-00342-7
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of COVID-19-associated rhino-orbital-cerebral mucormycosis: imaging analysis of 120 patients

Abstract: Background With the ongoing pandemic of COVID-19, there has been a rapid upsurge in cases of rhino-orbital-cerebral mucormycosis (ROCM). It is an opportunistic fungal infection associated with high morbidity and mortality. Rapid and appropriate application of clinical and radiological methods is crucial for early diagnosis, to limit the associated morbidity and improve post-treatment outcomes. In our study, we analyzed imaging features, common sites, and the extent of infection in patients suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…DM was also present in the majority of the patients with COVID-19-associated mucormycosis reported in the literature. 4,5,14,15 In our study, 2 of 8 patients were diagnosed with COVID-19-associated mucormycosis within 2 months of COVID-19 infection, 4 patients were diagnosed in the third month, 1 patient after 5 months, and 1 patient after 160 days of COVID-19 infection. Various surgical procedures that were performed in each of these patient as a part of the management protocol included bilateral (B/L) maxillectomy along with an alveolar process and hard palate removal (patient 1); B/L infrastructure maxillectomy þ B/L frontal sinusotomy (patient 2); right maxillectomy with orbital exenteration (patient 3); B/L maxillectomy involving anterior two-thirds hard palate with B/L frontal and ethmoidal sinusotomy (patient 4); B/L maxillectomy with B/L ethmoidal and maxillary sinusotomy (patient 5); right maxillectomy including alveolar process along with a bony defect wall of the maxillary and frontal sinus with right orbital exenteration (patient 6); right maxillectomy along with removal of the right zygoma, maxillary sinus, and right pterygoid plate (patient 7); and left suprastructure maxillectomy along with orbital exenteration (patient 8).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…DM was also present in the majority of the patients with COVID-19-associated mucormycosis reported in the literature. 4,5,14,15 In our study, 2 of 8 patients were diagnosed with COVID-19-associated mucormycosis within 2 months of COVID-19 infection, 4 patients were diagnosed in the third month, 1 patient after 5 months, and 1 patient after 160 days of COVID-19 infection. Various surgical procedures that were performed in each of these patient as a part of the management protocol included bilateral (B/L) maxillectomy along with an alveolar process and hard palate removal (patient 1); B/L infrastructure maxillectomy þ B/L frontal sinusotomy (patient 2); right maxillectomy with orbital exenteration (patient 3); B/L maxillectomy involving anterior two-thirds hard palate with B/L frontal and ethmoidal sinusotomy (patient 4); B/L maxillectomy with B/L ethmoidal and maxillary sinusotomy (patient 5); right maxillectomy including alveolar process along with a bony defect wall of the maxillary and frontal sinus with right orbital exenteration (patient 6); right maxillectomy along with removal of the right zygoma, maxillary sinus, and right pterygoid plate (patient 7); and left suprastructure maxillectomy along with orbital exenteration (patient 8).…”
Section: Discussionmentioning
confidence: 50%
“…Thus, it is anticipated that most of the survivors of COVID-19-associated mucormycosis will approach for reconstruction surgeries over a period of time. 1 Numerous cases series have described the clinical presentation, radiological investigations, neurological aspect, and management of patients with COVID-19associated mucormycosis, [4][5][6][7][8][9] and various local flaps like submental flap, facial artery musculomucosal flap, and various free flap including radial artery forearm free flap, deep circumflex iliac artery flap, anterolateral thigh (ALT) flap, and free fibula flap, but none of the studies have included details regarding the postoperative clinical outcomes of delayed reconstructive surgeries performed for rhino-orbito-maxillary (ROM) defects that occurred due to COVID-19-associated mucormycosis with DM. This study was conducted to evaluate the clinical outcomes in view of the quality of life, aesthetics, speech, and deglutition for short duration in patients with ROM defects due to COVID-19-associated mucormycosis with DM undergoing single stage delayed free flap reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, 59.6% of patients had periantral fat involvement. Agrawal et al showed periantral involvement in 75.83% of cases (15).…”
Section: Tablementioning
confidence: 96%
“…In our study, we also found variable signal intensity on T2WI (60% hyperintense, 25% isointense and 4% hypointense) and all showed hypointensity on T1WI. The accumulation of hemosiderin and paramagnetic materials such as calcium, iron, magnesium, and manganese has been linked to hypointensity on T1WI and T2WI in fungal disease (3,14,15).…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation